2020
DOI: 10.1007/s43032-020-00258-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of cAMP-Dependent Protein Kinase Inhibitor-b Promotes Preeclampsia by Decreasing Phosphorylated Akt

Abstract: Preeclampsia is a multi-system disease that is unique to human pregnancy. Impaired extravillous trophoblast migration and invasion accompanied by poor spiral vascular remodeling is thought to be the initial reason. This study investigated cAMP-dependent protein kinase inhibitor-b(PKIB) expression in placentas and its involvement in the pathogenesis of PE. We used immunohistochemistry and western blotting to calculate PKIB levels in the placentas. Then we knocked down PKIB by siRNA and used real-time cell analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…32 Decrease of cAMP-dependent protein kinase inhibitor-b (PKIB) promotes PE by inhibiting the migration, invasion, and vascularization of HTR-8/ SVneo trophoblast cells by reducing phosphorylated AKT. 33 The PI3K/AKT pathway was also associated with the expression of sFlt-1, which plays a crucial role in PE. 34 From the WB data, OE of LINC00534 significantly inhibited the phosphorylation of p110β (the catalytic subunits of PI3K) and AKT protein, while knockdown of LINC00534 showed the opposite effect, indicating that LINC00534 can negatively regulate the activation of the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 Decrease of cAMP-dependent protein kinase inhibitor-b (PKIB) promotes PE by inhibiting the migration, invasion, and vascularization of HTR-8/ SVneo trophoblast cells by reducing phosphorylated AKT. 33 The PI3K/AKT pathway was also associated with the expression of sFlt-1, which plays a crucial role in PE. 34 From the WB data, OE of LINC00534 significantly inhibited the phosphorylation of p110β (the catalytic subunits of PI3K) and AKT protein, while knockdown of LINC00534 showed the opposite effect, indicating that LINC00534 can negatively regulate the activation of the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Syntaxin2 (STX2) activates the PI3K/AKT pathway through membrane recruitment of p85 (a regulatory subunit of PI3K), promotes trophoblast cell proliferation, migration, and invasion, and participates in the mechanism of PE 32 . Decrease of cAMP‐dependent protein kinase inhibitor‐b (PKIB) promotes PE by inhibiting the migration, invasion, and vascularization of HTR‐8/SVneo trophoblast cells by reducing phosphorylated AKT 33 . The PI3K/AKT pathway was also associated with the expression of sFlt‐1, which plays a crucial role in PE 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The genes associated with proteolytic activity are as follows: CRISP3 encoding a protein with homology to plant defense proteins with lytic activity against infectious pathogens [ 53 ]; CSTA encoding cystatin A, a cysteine proteinase inhibitor that belongs to a large family of the cystatin superfamily [ 54 ]; CTSD encoding cathepsin D, a lysosomal aspartic protease with many additional functions such as those in cell proliferation, invasion, metastasis, and angiogenesis of cancers [ 55 ]; TMPRSS3 encoding a Type II transmembrane serine protease, a membrane-bound proteolytic enzyme that is associated with biological processes such as poor prognosis in patients with breast cancer [ 56 , 57 ]. The genes associated with protein kinase activity and related cellular signaling are: PKIB encoding a protein acting as a competitive inhibitor of the cAMP-dependent protein kinase, which plays important roles in cell signaling in diseases such as the down-regulation of Akt signaling in irritable bowel syndrome [ 58 ], preeclampsia [ 59 ], and cancers [ 60 – 62 ]; PKIB encoding a competitive inhibitor of cAMP-dependent protein kinase involved in breast cancer development by enhancing ERα action [ 63 ]; RAB26 encoding a RAB-family small GTPase that regulates intercellular vesicle trafficking, including exocytosis, endocytosis, and recycling [ 64 ]; RAP1GAP encoding a GTPase-activating protein (GAP) that promotes the hydrolysis of GTP in RAP1-GTP and inactivates RAP1, which plays important roles in the regulation of cell adhesion and migration and in the progression and metastasis of several types of cancer [ 65 ]; RAPGEFL1 encoding a protein with predicted guanyl-nucleotide exchange factor (GEF) activity, which promotes RAP1 to load GTP and acquire the active GTP-bound status [ 66 ]; RAPGEFL1 , a gene found in several types of cancer, acting as an estrogen-regulated gene in breast cancer cells [ 67 ]; SRGAP3 encoding a protein highly expressed in the brain, with structural characteristics of BAR/Rac1 GAP/SH3 domains and considered to be a tumor suppressor in breast cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis showed that these 159 genes were significantly enriched in multiple pathways including cytokine-cytokine receptor interaction, nucleotide excision repair, viral myocarditis, and Tolllike receptor/PI3K-AKT/MAPK/Wnt signaling pathways, suggesting the vital roles of NR_002794 in these pathways. AKT and ERK1/ 2 signaling pathways have been found to be involved in the regulation of PE and trophoblast development [30][31][32]. For instance, the inhibition of the PI3K/AKT pathway by LY294002 led to the notable reduction of cell proliferative and invasive abilities and a marked increase of cell apoptotic percentage in HTR-8/SVneo trophoblast cells [33].…”
Section: Discussionmentioning
confidence: 99%